2014
DOI: 10.4041/kjod.2014.44.5.236
|View full text |Cite
|
Sign up to set email alerts
|

En-masseretraction with a preformed nickel-titanium and stainless steel archwire assembly and temporary skeletal anchorage devices without posterior bonding

Abstract: ObjectiveTo evaluate the therapeutic effects of a preformed assembly of nickel-titanium (NiTi) and stainless steel (SS) archwires (preformed C-wire) combined with temporary skeletal anchorage devices (TSADs) as the sole source of anchorage and to compare these effects with those of a SS version of C-wire (conventional C-wire) for en-masse retraction.MethodsThirty-one adult female patients with skeletal Class I or II dentoalveolar protrusion, mild-to-moderate anterior crowding (3.0-6.0 mm), and stable Class I p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…12 With the better stability and the less stress concentration than conventional screws, spike screw could be used in expansion periods without loosening. Moreover, compared with another kind of high stability sand blasted, large grit with acid-etched surfacetreated screw C-implant, 13 the spike screw do not need 4 weeks healing time, because it does not need osseointegration. Over 3.5 mm in diameter, tissue punching device, however, is necessary for placing 5 mm in diameter washers during spike screw application.…”
Section: Discussionmentioning
confidence: 96%
“…12 With the better stability and the less stress concentration than conventional screws, spike screw could be used in expansion periods without loosening. Moreover, compared with another kind of high stability sand blasted, large grit with acid-etched surfacetreated screw C-implant, 13 the spike screw do not need 4 weeks healing time, because it does not need osseointegration. Over 3.5 mm in diameter, tissue punching device, however, is necessary for placing 5 mm in diameter washers during spike screw application.…”
Section: Discussionmentioning
confidence: 96%
“…The CHretractor was developed, which combines the anterior NiTi sectional and posterior SS archwires, using gable bends for effective control of the anterior teeth. 8 Without a gable bend, a retraction force (F H ) generates a clockwise moment (M FH ), because the force vector passes below the center of resistance (CR) of the six anterior teeth ( Figure 6A). This moment leads to anterior torque loss (see 08 gable bend on Table 4) and an extrusion tendency of anterior teeth (see 08 gable bend on Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 8 the clinical efficiency of the preformed SS C-wire was reported for the treatment of dentoalveolar protrusion patients who have stable Class I molar relationships. With the CH-retractor, simultaneous alignment, leveling, and space closure are possible from the day appliances are placed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of temporary skeletal anchorage devices (TSADs) in orthodontics has made the mechanics of treatment simpler and more effective than conventional techniques [ 1 – 3 ]. Orthodontic mini-implants, which are generally made of a titanium alloy, are cylindrically shaped with a diameter of 1.5–2.0 mm and a length of 6.0–9.0 mm [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The known risk factors for failure are root proximity, insertion site, and inflammation of the peri-implant soft tissue. Many attempts have been made to increase the survival rate of mini-implants [ 1 – 3 , 9 ]. Studies have shown that the healing period between mini-implant insertion and orthodontic force application is not critical.…”
Section: Introductionmentioning
confidence: 99%